2016
DOI: 10.1515/ncrs-2016-0100
|View full text |Cite
|
Sign up to set email alerts
|

Structure and photochromism of 1-(1,2-dimethylindol-3-yl)-2-[2-methyl-5-(3-fluorophenyl)-3-thienyl]-3,3,4,4,5,5-hexafluorocyclopent-1-ene, C26H18F7NS

Abstract: C 26 H 18 F7NS, triclinic, P¯ , a = 8.492(18) CCDC no.: 1496664The crystal structure is shown in the gure. Tables 1 and 2 contain details of the measurement method and a list of the atoms including atomic coordinates and displacement parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Up to date, scienctists have designed and synthesized many new diarylethenes. It is reported that some of them can exhibit the properties of photochromism in solid state and in solution [18]. However, some of them cannot show the photochromism in solid state, but they can represent good photochromism characteristics in solution [19].…”
Section: Commentmentioning
confidence: 99%
“…Up to date, scienctists have designed and synthesized many new diarylethenes. It is reported that some of them can exhibit the properties of photochromism in solid state and in solution [18]. However, some of them cannot show the photochromism in solid state, but they can represent good photochromism characteristics in solution [19].…”
Section: Commentmentioning
confidence: 99%
“…The result demonstrated that the photochromic characteristics of diarylethenes strongly depend on the kind of the heteroaryl moieties and their substituents [18,19]. Some research reported found that part of them can exhibit the properties of photochromism in solid state and in solution [20]. However, some of them cannot show the photochromism in solid state, but they can represent good photochromism characteristics in solution [21].…”
Section: Commentmentioning
confidence: 99%